Can whole genome sequencing resolve taxonomic ambiguities in fungi? The case study of Colletotrichum associated with ferns - Menicucci, Andrea; Iacono, Salvatore; Ramos, Madalena; Fiorenzani, Chiara; Peres, Natalia Aparecida; Timmer, Lavern Wayne; Prodi, Antonio; Baroncelli, Riccardo (Frontiers in Fungal Biology, 2025)
IntroductionThe genus Colletotrichum comprises numerous fungal species with diverse ecological roles, including plant pathogenic, endophytic, and saprophytic lifestyles. Accurate species identification is crucial for understanding host-pathogen interactions, disease epidemiology, and fungal ecology. However, taxonomic classification within Colletotrichum remains challenging due to genetic complexity and phenotypic plasticity. Conventional approaches such as single-gene analyses and multilocus sequence typing (MLST) frequently fail to resolve closely related taxa, leading to misidentifications that hinder species delimitation and comparative evolutionary studies. Whole-genome sequencing (WGS) offers a promising alternative by providing genome-wide resolution for phylogenetic analysis. This study investigates Colletotrichum isolates associated with the fern Rumohra adiantiformis and evaluates the effectiveness of WGS in addressing taxonomic uncertainties.MethodsA total of 18 Colletotrichum isolates, including fern-associated strains, were analyzed. Genomic DNA was extracted and sequenced using the Illumina NovaSeq platform. High-quality genome assemblies were generated, and gene prediction was conducted using AUGUSTUS. Orthogroup assignment and phylogenomic analysis were performed based on single-copy orthologs, and phylogenetic trees were constructed using MLST and WGS-based approaches. Comparative analyses were carried out to assess the taxonomic resolution provided by WGS in relation to traditional methods.ResultsGenome-wide phylogenomic analysis revealed distinct evolutionary lineages among Colletotrichum isolates that MLST failed to resolve, highlighting host and geographic differentiation. High-quality genome assemblies were obtained, with 98.3% of genes assigned to orthogroups, indicating strong genomic conservation. Phylogenetic analyses confirmed a close relationship between Rumohra adiantiformis-associated isolates and Colletotrichum filicis, reinforcing the effectiveness of WGS in species identification.DiscussionThese findings demonstrate the superiority of WGS over MLST in resolving species boundaries and reconstructing evolutionary relationships. The enhanced resolution provided by genome-wide data enables more accurate taxonomic classification, reducing misidentifications and improving our understanding of fungal biodiversity. By refining Colletotrichum taxonomy, WGS facilitates ecological and pathogenic studies, offering a robust framework for future research in fungal systematics and plant pathology. As sequencing technologies continue to advance, WGS is expected to become a standard tool for fungal species delineation and evolutionary studies.